The Effect of The Addition of Bagasse Ash on The Making of Paving Block - Agustapraja, Hammam Rofiqi; Pramono, Djoko Heru; Wahab, Izudinshah Abd. (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2024)
Paving Concrete is a composite of building materials made from a mixture of Portland cement or adhesive, water, and aggregate with or without other additives, which do not reduce the quality of the Concrete. In the research, fc' K-175 kg/cm2 of bagasse ash was added with variations of 0%, 6%, 8%, and 12% bagasse ash; the weight is based on the weight of the cement. This study aimed to determine the compressive strength of Concrete obtained from a mixture of bagasse ash in K-175 kg/cm2. The concrete mix design refers to SNI-03-0691-1996. Test samples prepared for each additional percentage of bagasse ash were three samples in the form of cubes with a length of 20 cm, a height of 8 cm, and a width of 10 cm. The results showed a decrease in strength with each addition of bagasse ash. It is known that the average compressive strength of Concrete after 28 days is 176.66%. Kg/m2 and the lowest compressive strength were obtained by adding 12% ash from bagasse aged 28 days, which was 73.33 kg/m2.